The Effect of Price Fluctuations and the Pricing System on the Income of Oil Palm Farmers in Bunde Village, Sampaga District, Mamuju Regency - Muh. Syahrul; Nur Asia; J. Fuji Inzani SL; Andi Indra Martini; Nur Fajariani (Economics and Digital Business Review, 2026)
This research was undertaken to examine how price fluctuations and the pricing system, both separately and jointly, shape the income earned by oil palm growers in Bunde Village, Sampaga District, Mamuju Regency. Adopting a quantitative associative research design, the study treated the entire body of oil palm farmers in the village—whose precise number could not be ascertained (an infinite population)—as its target population, from which 50 respondents were drawn by means of accidental sampling in accordance with the Roscoe guideline. Information was gathered through field observation, direct interviews, documentary review, and the distribution of a questionnaire measured on a five-point Likert scale, and was subsequently processed through multiple linear regression, partial (t) testing, simultaneous (F) testing, and the coefficient of determination, after the measuring instrument had passed validity and reliability screening. The analysis reveals that price fluctuations exert a positive and statistically significant partial influence on farmers’ income (t = 2.693; sig. 0.010), while the pricing system likewise produces a positive and significant partial influence (t = 2.443; sig. 0.018). Taken together, the two variables significantly determine farmers’ income (F = 14.773 > 3.195; sig. 0.000), accounting for 38.6 percent of its variation, with the residual 61.4 percent attributable to determinants lying beyond the model. These results imply that stabilizing prices and instituting a transparent and equitable pricing arrangement constitute strategic levers for improving the welfare of smallholder oil palm farmers.